The Effect of Supply Chain Management on the Performance of Commercial Bank Organization in Ethiopia's Case of Jimma City - Sultan Jemal (Goodwood Publishing, 2022)
Purpose: the main purpose of this research was to examine the impact of supply chain management (SCM) practice on performance in bank organizations in Ethiopia. Research methodology: Cross-sectional descriptive survey design was employed and three purposively selected government banks were studied using a census sampling approach, the data was collected through pretested questionnaire. The main quantitative analysis was employed using STATA 14. Results: status of SCM practice was at a high level. Spearman correlation analysis revealed that ease of access system support, efficient ordering, lean program, lead time, and customer relationship uniting SCM best practice with profitability have a positive relationship, however ordinal logistic regression analysis revealed that SCM practice dimensions customer relationship with SCM best practice and lean program have a positive significant impact on the profitability of bank organization. Limitations: The study performed at Jimma city may not represent all business process office employees of the bank and further longitudinal study required Contribution: This study offers practical and vital means for supply chain managers to appraise and measure supply chain performance practices. For instance, SCM practices can be employed to assess the degree to of firms' performance practices have been achieved and their impact on enhancing satisfaction.